2021
DOI: 10.1038/s41421-020-00227-0
|View full text |Cite
|
Sign up to set email alerts
|

Structure, substrate specificity, and catalytic mechanism of human D-2-HGDH and insights into pathogenicity of disease-associated mutations

Abstract: D-2-hydroxyglutarate dehydrogenase (D-2-HGDH) catalyzes the oxidation of D-2-hydroxyglutarate (D-2-HG) into 2-oxoglutarate, and genetic D-2-HGDH deficiency leads to abnormal accumulation of D-2-HG which causes type I D-2-hydroxyglutaric aciduria and is associated with diffuse large B-cell lymphoma. This work reports the crystal structures of human D-2-HGDH in apo form and in complexes with D-2-HG, D-malate, D-lactate, L-2-HG, and 2-oxoglutarate, respectively. D-2-HGDH comprises a FAD-binding domain, a substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 54 publications
1
23
0
Order By: Relevance
“…In the present study, metal-bound P. aeruginosa PAO1 D2HGDH has been characterized in its kinetic properties using steady-state and rapid-reaction kinetics and investigated for the effects of solvent viscosity, pH, and deuterated solvent on its kinetic parameters. The results presented are consistent with the minimal catalytic mechanism of Figure 7 , which also considers recently reported structural data ( 18 , 77 ). In the resting state, the active site Zn 2+ coordinates to H 374 , H 381 , E 420 , the flavin O 4 atom, and a hydroxide ion.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, metal-bound P. aeruginosa PAO1 D2HGDH has been characterized in its kinetic properties using steady-state and rapid-reaction kinetics and investigated for the effects of solvent viscosity, pH, and deuterated solvent on its kinetic parameters. The results presented are consistent with the minimal catalytic mechanism of Figure 7 , which also considers recently reported structural data ( 18 , 77 ). In the resting state, the active site Zn 2+ coordinates to H 374 , H 381 , E 420 , the flavin O 4 atom, and a hydroxide ion.…”
Section: Discussionsupporting
confidence: 92%
“…By gas chromatography-mass spectrometry (GC-MS), we found that Δ dhgd-1 mutants accumulate about five-fold more 2HG than wild type animals ( Figure 1C ). Human D2HGDH specifically oxidizes the D-form of 2HG to αKG (Yang et al, 2021). To test the stereo-specificity of C. elegans DHGD-1, we used chiral derivatization that allows the chromatographic separation of the D- and L-2HG enantiomers.…”
Section: Resultsmentioning
confidence: 99%
“…1c). Human D2HGDH specifically catalyzes the conversion of the D-form of 2HG 12 . To test the stereo-specificity of C. elegans DHGD-1, we used chiral derivatization that allows the chromatographic separation of the D-and L-2HG enantiomers.…”
mentioning
confidence: 99%
“…Beyond reducing 2-KG to d -2-HG, in many organisms, SerA can also reduce oxaloacetate to d -malate 14 . Given the importance of l -serine in metabolism, D2HGDH in these organisms has evolved to be a versatile enzyme capable of dehydrogenating both d -malate and d -2-HG to eliminate these two metabolites 48 . Interestingly, D2HGDH in A. denitrificans NBRC 15125 has no d -malate dehydrogenation activity and only participates in exogenous d -2-HG catabolism.…”
Section: Discussionmentioning
confidence: 99%